The confession - Spain, Jo (Crooked Lane, 2018)
"Late one night a man walks into the luxurious home of disgraced banker Harry McNamara and his wife Julie. And when the man launches an unspeakably brutal attack on Harry, a horror-struck Julie, frozen by fear, watches her husband die. Just one hour later, the attacker, J. P. Carney hands himself into the police and confesses to beating Harry to death. Except he also claims that the assault was not premeditated and that he didn't know the identity of his victim. With a man as notorious as Harry McNamara, who was just found innocent in a highly sensationalized fraud trial, the detectives cannot help but wonder: Was this really a random act of violence? Was Julie really powerless to stop JP? When Harry's many sins are unveiled to include corruption, greed, and betrayal, nothing is for sure. This gripping psychological thriller will have you questioning, who--of Harry, Julie and JP--is really the guilty one? And is Carney's surrender driven by a guilty conscience or is his confession a calculated move in a deadly game?" -- publisher.